My Nationality or My Ethnicity? The Pride and Attitudes of Balinese Youth as Citizen of Indonesia - Surijah, Edwin Adrianta; Ayuningtias, Agnes Utari Hanum; Hartika, Listiyani Dewi; Suryani, Angela Oktavia (UI Scholars Hub, 2019)
Prior research on national identity focused on immigrants and racial discrimination. The current study aims to analyze national identity in Indonesia, a country with various ethnicities, especially on Bali. We hypothesized that multicultural attitudes, ethnic identity, and multicultural communication predict national identity. Four hundred undergraduate students completed the questionnaires. Data was analyzed with regression analysis entry method. Our hypothesis was partially supported. The contextual concept and understanding were discussed in explaining the research findings along with its implications